Protección de datos personales y derecho al olvido. Análisis del caso Perú vs. Google (Jurisprudencia) - Cuenca Espinosa, Alexander (2017)
The main objective of this article is aimed at analyzing the appeal of reconsideration raised by the appellant (Google Peru SRL) in the case of Peru vs. Google, reason why the complainant denounces the non-cancellation of personal data, which affect its public image against Google Perú SRL, when the latter does not carry out the activity that has to do with the indexing of information in search engines, since that is the work of Google Inc. resident at EE. UU. To which no legal notice arrives, leaving it in a state of defenselessness. In this area, it also refers to the sanctioning resolution while considering ARCO rights with respect to the owner of the action, does not take into account the right to defend the recurrence and freedom of expression.